ISLAMIC SPIRITUAL PERSPECTIVE: CHANGE MANAGEMENT FOR MICRO, SMALL AND MEDIUM ENTERPRISES - Wikaningtyas, Suci Utami; Sulastiningsih , Sulastiningsih; Maududi, Arsyilala Al Maududi; Larasshati, Kinanthi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Micro, Small, and Medium Enterprises (MSMEs) operating in Indonesia are confronted with significant challenges arising from the dynamic landscape, particularly in relation to technology advancements. Therefore, it is imperative for MSME players to implement Kubler-Ross change management. The employed research methodology entails the utilization of descriptive qualitative analysis. Based on empirical data, it is evident that certain actors within the MSME sector are currently experiencing states of ill-being, characterized by emotions such as shock, denial, frustration, and depression. In order to ensure their survival, players in the Micro, Small, and Medium Enterprises (MSMEs) have to undergo a transformation towards achieving well-being, namely through the process of integration, which necessitates the implementation of various strategies for change. However, considering the population of Indonesia, about 90 per cent of which is Muslim, change management in Islamic spiritual perspective is the most suitable to be utilized.